Literary genres and teaching Portuguese as a foreign language in teletandem - Ramos, Karin Adriane Henschel Pobbe [UNESP]; Diaz, Anelly Mendoza; da Silva, Mayara Nunes [UNESP] (Springer Nature, 2023)
This chapter aims to discuss an experience of circulation of literary genres in the context of virtual exchange on teletandem (Telles, Teletandem: Um contexto virtual, autônomo e colaborativo para aprendizagem de línguas estrangeiras no século XXI. Pontes Editores, Campinas, 2009), observing how reading and sharing these genres can contribute to enhance interactions in this process. The experience discussed in this work is based on data collected in teletandem interactions between students from a Brazilian university and students from a Mexican university. Therefore, we assume an intercultural discourse perspective (Kramsch & Hua, Routledge handbook of English language teaching. Routlege, London, 2016) for language teaching and emphasize the humanizing function of literature (Candido, Ciência e Cultura 24(09):803-809, 1972, Vários Escritos, 5. Ouro sobre Azul, Rio de Janeiro, 2011), considering that it can act directly in the formation of the subject. Data analysis and discussion indicate that inserting literary texts in tandem sessions enables a deepening of discussions and the emergence of more diverse themes directly related to the realities of the participants.
Keywords: Foreign language teaching; Literary genres; Literature; Portuguese as a foreign language; Teletandem